Modeling Interrill Erosion on Unpaved Roads in the Loess Plateau of China. (10th October 2013) - Cao, Longxi; Zhang, Keli; Dai, Hailun; Liang, Yin
Abstract: Unpaved roads play an important role in soil loss in small watersheds. In order to assess the impact of these unpaved roads in the Loess Plateau of China, runoff and sediment yields from road‐related sources must be quantified. Field rainfall simulation experiments were conducted under three slope gradients and five rainfall intensities on unpaved loess roads in a small watershed. Results showed that the runoff generation was very fast in loess road surface (time to runoff < 1 min) and produced a high runoff coefficient (mean value > 0·8). Soil loss rates were decreased as surface loose materials were washed away during a rainstorm. Rainfall intensity, initial soil moisture, and slope gradient are key factors to model surface runoff and sediment yield. Soil loss on loess road surface could be estimated by a linear function of stream power ( R 2  = 0·907). Four commonly interrill erosion models were evaluated and compared, and the interrill erodibility adopted in the Water Erosion Prediction Project model was determined as 1·34 × 10 6 (kg s m −4 ). A new equation taking into account different parameters like rainfall intensity, surface flow discharge, and slope gradient was established. Copyright © 2013 John Wiley & Sons, Ltd.